The Dark-Plate Method of Relief Portrayal - Wilson, Joe Frank (The International Hydrographic Review, 2018)
The dark-plate method of relief portrayal was developed to provide in a one-color press run the maximum tonal range from highlight to shadow for application of relief shading to the nautical charts of the U.S. Navy Hydrographic Office. This tonal range is achieved by scraping away or intensifying with wax crayon a grey coating printed lithographically on translucent vinyl plastic. The method is described as being effective and economical, and especially suited for relief portrayal of areas presenting problems in relief shading by other methods.